2015
DOI: 10.1002/cam4.439
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and survival of patients with brain metastasis from breast cancer who underwent craniotomy

Abstract: Brain metastasis (BM) in patients with breast cancer is a catastrophic event that results in poor prognosis. Identification of prognostic factors associated with breast cancer brain metastases (BCBM) could help to identify patients at risk. The aim of this study was to assess clinical characteristics, prognostic factors, and survival of patients with BCBM who had craniotomy and resection in a series of patients treated with modern multimodality therapy. We analyzed 42 patients with BCBM who underwent resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 30 publications
8
57
0
2
Order By: Relevance
“…It is important to note that triple-negative breast cancer patients commonly develop secondary tumors in peripheral organs (liver, bone, lung), 31 beyond brain metastases that often arise later during the disease progression. 32 For this reason, it has been suggested that breast cancer tumor cells need some time to develop their ability to penetrate through the BBB and colonize the brain. 33 In this frame, it would be interesting to investigate and compare the ability of metastatic breast cancer cells to interact with the endothelium from different organs (adhesion, transmigration processes).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that triple-negative breast cancer patients commonly develop secondary tumors in peripheral organs (liver, bone, lung), 31 beyond brain metastases that often arise later during the disease progression. 32 For this reason, it has been suggested that breast cancer tumor cells need some time to develop their ability to penetrate through the BBB and colonize the brain. 33 In this frame, it would be interesting to investigate and compare the ability of metastatic breast cancer cells to interact with the endothelium from different organs (adhesion, transmigration processes).…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases in breast cancer generally represent a catastrophic event that presages dismal survival [10][11][12][13][14]. However, this malignancy represents a group of disease with substantial A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 biological and clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Leone ve ark., meme kanserinin teşhis anındaki evresi yüksek oldukça, teşhis ile beyin metastazı gelişmesi arasındaki sürenin o kadar kısa olduğunu göstermişlerdir (10). Nishimura ve ark., beyin…”
Section: Discussionunclassified